THE EFFECT OF DISTANCE EDUCATION APPLICATIONS BASED ON SMART BOARD ON STUDENTS' ACHIEVEMENT AND SKILLS IN PATTERN PREPARATION TECHNIQUES - Celikoz, Nadir; Gursoy, Fatma (ANADOLU UNIV, 2014)
The aim of this study is to find out the effect of distance education applications based on smart board in teaching pattern preparation techniques and its contribution to students' achievement and skills. An experimental model with a pretest-posttest experimental and control group was used with 34 students who attended the department of Ready-Made Clothing Teacher Training Programme at Selcuk University in Turkey. As experiment group, distance education model by using the smart board was applied to the students synchronously. The students in the control group had the same lessons in traditional way in the classroom. The data was obtained using the achievement test, applied exam and skill observation form developed by the researchers and evaluated statistically with the help of Wilcoxon Signed Ranks and Mann Whitney-U tests. The findings obtained after a four-week-application indicate that the synchronous distance education model by using smart board has been more effective on student achievements than the traditional way.
Keywords: Synchronous Distance Education; Smart Board; Pattern Preparing Techniques; Student Achievement; Student Skill; Education & Educational Research